Thoracentesis of Large Volume Tuberculous Pleural Effusions - Awan, Abdul Khalid; Baqai, Mohammad Tariq; Bukhari, Murtaza (International Journal of Pathology, 2018)
AbstractObjective: To determine the safety of aspiration of large volume pleural effusion.Study design: Prospective, observational, multicentre study.Place and duration of study: Departments of Medicine Abbas Institute of Medical Sciences (AIMS) Muzaffarabadand District Head Quarter Hospital Mirpur Azad Jammu and Kashmir from January 2012 to October2012Material and Methods: The study wasconducted in two teaching hospitals of AJK. During this study periodthoracentesis of large volume pleura fluid was performed in 97 patients.Results: During thoracentesis of more than 1 Litre pleural fluid, 95% patients remained asymptomatic andhemodynamically stable. One patient had a small asymptomatic pneumothorax. Three patients had mild chestpain which settled on termination of procedure.Conclusion: Aspiration of large volume pleural fluid is a safe procedure.